The impact of prior sexual victimization and victim identification on threat recognition in a college sample - Porter, Katherine (2010)
Previous research on sexual assault has demonstrated a pattern of revictimization, in which victims of childhood sexual assault are at an increased risk for adult sexual assault (e.g., Tjaden & Thoennes, 2000). Previous findings indicate that participants with a history of sexual assault take longer to identify and respond to risks (Marx et al., 2001; Soler-Baillo et al., 2005; Wilson et al., 1999), are less likely to respond in assertive ways (VanZile-Tamsen et al., 2005), and are more likely to indicate that they would be compliant in risky sexual situations (Naugle, 1999). The present study attempted to replicate and expand this literature by investigating psychological variables that have been previously theoretically and/or empirically linked to revictimization to assess their impact on how female college students perceived and responded to risk in dating scenarios, as well as assessing difference between the perceived risk and consequence. This study was completed in two phases online. In total 111 students completed the full study. Results indicated that students did not differ in their overall perception of risk based on their assault status, but those with a history of assault took statistically significantly longer to indicate that they would choose to leave. Additionally, when asked to predict what would happen if the scenario continued, participants with a history of assault were significantly more likely to predict that the characters would have consensual sex. They were also more likely to indicate that the female in the scene may miss out on a meaningful relationship if she chose to leave